Penguatan Peran Orang Tua dan Masyarakat Melalui ABCD untuk Mengatasi Faktor Penyebab Anak Tidak Bersekolah di Desa Situhiang - Rijaal Qurrota A’yuni; Dea Nurazizah; Bayu Cahyadi; Abdul Rohman; Hasni Radhwatul Awaliyah (Lembaga Pengembangan Kinerja Dosen, 2025)
The phenomenon of children not attending school in Situhiang Village is still a serious problem that has an impact on the social, emotional, and sustainable development of children's education. This service program aims to design and implement mentoring based on the Asset Based Community Development (ABCD) approach by involving parents, teachers, and the community as the main subjects in overcoming the causes of children not attending school. The ABCD method is used through the stages of asset mapping, expectation formulation, strategy design, action plan determination, and implementation of continuous mentoring. The results of the activity showed that the main causes of school absenteeism were related to children's negative experiences, family economic conditions, and social environmental pressures. Mentoring has succeeded in increasing parental awareness, strengthening community support, and creating a safer, more comfortable, and child-friendly learning environment. This program also fosters the collective commitment of residents to maintain the sustainability of education through the formation of education care groups. These findings confirm that community empowerment through an asset-based approach is effective in reducing children's risk of school dropouts, increasing primary education participation, and encouraging children's social inclusion in the community.